ANALISIS DAMPAK PENCEMARAN UDARA TERHADAP KESEHATAN MASYARAKAT DI PERKOTAAN - Rahmawati, Vina; Hayat, Ade Luvita; Salam, Aldi (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
Air pollution in urban areas has become a serious public health problem. Public health impacts can include acute and chronic respiratory diseases, cardiovascular diseases, lung cancer, and even death. This study aims to analyze the impact of air pollution on urban public health. The method used in this study is a literature review by examining various sources of data, such as scientific journals, government reports, and health statistics. data. The results show that air pollution has a significant impact on the health of urban communities, especially for vulnerable groups such as children, the elderly and those with the poorest health conditions. The study also showed that air pollution levels in urban areas are often higher than in rural areas. This is due to various factors, such as population density, industrial activity and motor vehicle emissions. Based on the results of the study, it can be concluded that air pollution is a public health issue that needs special attention from the Government and different stakeholders. Efforts to reduce air pollution must be carried out in a sustainable manner, for example by improving the quality of public transportation, encouraging the use of renewable energy and implementing stricter pollutant emission regulations.